Development of Sparkol Videoscribe-Based Learning Media in Enhancing Arabic Vocabulary Mastery for Eighth Grade Students - Assyifa, Adelia; Fauziah, Asti; Qubaiyah, Namirotul (WISE Pendidikan Indonesia, 2023)
In Arabic language learning at school, the role of the teacher in delivering and presenting the materials to be taught has a significant influence on students' learning outcomes. Factors contributing to weak Arabic vocabulary mastery include difficulties in memorizing vocabulary due to students' reliance solely on school-based learning, lack of interest and motivation for learning, memorizing, and recalling Arabic vocabulary, as well as students' school backgrounds without Arabic language subjects. Therefore, it is necessary to employ engaging teaching methods or media to deliver the material to students. This research aims to develop, assess the feasibility, and evaluate the attractiveness of Arabic vocabulary learning material based on Sparkol Videoscribe media. This study is a developmental research that utilizes the ADDIE model, which emphasizes the analysis of how each component interacts coordinatively with the existing phases. The research was conducted at Daarul Ilmi Integrated Islamic Junior High School in Bandar Lampung in November 2022. The developed media has been proven suitable for use, with material expert validation results of 76% or deemed suitable, media expert validation results of 78% or deemed suitable, and educator validation results of 88% or highly suitable. Based on the trial results conducted to determine the attractiveness of Sparkol Videoscribe-based learning media in Arabic language classes for eighth graders, it obtained a score of 86% in small group trials and 89% in large group trials, categorizing it as highly attractive. Thus, the results of Sparkol Videoscribe-based learning media are attractive for student use and can facilitate the mastery of Arabic vocabulary.